IR spectrometric studies of glass transition of freon CF3-CFH2 - Shinbayeva, A.K.; Aldiyarov, A.U.; Drobyshev, A.S.; Nurmukan, A.E. (Recent Contributions to Physics, 2018)
IR spectroscopic studies of structural-phase transformations in cryocondensed Freon films 134a were carried out. The investigations were carried out in the temperature range 16-100 K. Was discovered, that freon cryofilms 134a, formed at T = 16K, under heating in the temperature range from 70 to 90 K undergo multiple structural transformations of various nature. It is concluded that at a temperature of Tg = 72 K, a transition of the glassy state to a supercooled liquid (G-SCL) takes place. At a temperature near T = 78 K, crystallization of SCL into the state of an orientationally disordered plastic crystal begins. At a temperature Ttrans = 80 K, a second quasi-glass transition occurs from the state of the orientation glass to a plastic crystal with an ordered rotational subsystem. In the temperature range 83-85 K, a plastic crystal-monoclinic crystal phase transition is realized.
Keywords: freon, glass transition, IR spectra